Association between tinnitus and cognitive impairment: analysis of National Health and Nutrition Examination Survey 2011:2014 - Wu, Jianli; Shi, Mengdi; Wang, Chao (Frontiers in Neurology, 2025)
BackgroundTinnitus is one of the most common potential risk factors for cognitive impairment. To understand the relationship between tinnitus and cognitive impairment, the National Health and Nutrition Examination Survey (NHANES) database was analyzed after adjusting for potential confounders, including age and other systemic comorbidities.Materials and methodsA total of 684 participants who had undergone a total tinnitus survey and underwent a cognitive function test were included. Tinnitus is divided into acute tinnitus and non-acute tinnitus. The Consortium for the Establishment of Alzheimer’s Disease Word Learning Xi Registry (CERAD-WL), the Dynamic Logistics Proficiency Test (AFT), and the Digit Sign Substitution Test (DSST) were used to assess cognitive impairment.ResultsSubjects with tinnitus had lower AFT and DSST scores compared to the healthy group, indicating decreased cognitive function. After adjusting for other covariates in humans, tinnitus was significantly associated with a decrease in AFT and DSST scores (trend p-values = 0.02 and 0.005, respectively).ConclusionTinnitus is associated with cognitive impairment.